Pars plana vitrectomy in management of giant retinal tear and retinal detachment following iris-fixated anterior chamber phakic intraocular lens implantation - Sen, Sagnik (BMJ Case Rep, 2018)
This case report describes a 26-year-old man presenting with a giant retinal tear (GRT) with retinal detachment (RD) following implantation of iris-fixated anterior chamber phakic intraocular lens (AC-PIOL) for high myopia and occurrence of intraoperative aberrations during vitrectomy due to the presence of AC-PIOL in situ. Posterior chamber PIOL have been well reported to be associated with GRT with RD. Very few reports exist of GRT with RD following AC-PIOL. Moreover, the presence of iris-fixated AC-PIOL, in this case, led to the formation of ghost images intraoperatively especially during crucial steps like induction of posterior vitreous detachment which has never been reported.